2021
DOI: 10.1177/0361198120985848
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Elastic Modeling of Rail and Fastener Longitudinal Response

Abstract: The rail fastening system plays a critical role in maintaining proper railroad track geometry by transferring vertical, lateral, and longitudinal forces from the rails to crossties. Broken spikes in elastic fastening systems have been linked to inadequate transfer of longitudinal loads, posing a safety risk for timber crosstie ballasted track. Longitudinal track demand caused by passing trains has been investigated in previous research, but the magnitude and distribution of longitudinal fastener loads is not w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 8 publications
0
19
1
Order By: Relevance
“…Dersch et al quantified the vertical, lateral, and longitudinal rail and fastener loads at one given location ( 32 ), and Khachaturian et al quantified the effect of fastening system stiffness on longitudinal fastener load magnitude ( 17 ). However, in both cases, the researchers leveraged a one-dimensional (1D) analytical model that was validated by Trizotto et al’s limited model ( 33 ).…”
Section: Objective and Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Dersch et al quantified the vertical, lateral, and longitudinal rail and fastener loads at one given location ( 32 ), and Khachaturian et al quantified the effect of fastening system stiffness on longitudinal fastener load magnitude ( 17 ). However, in both cases, the researchers leveraged a one-dimensional (1D) analytical model that was validated by Trizotto et al’s limited model ( 33 ).…”
Section: Objective and Motivationmentioning
confidence: 99%
“…Additionally, track resistance is simplified by representing the fastener and ballast as a single, combined spring. This approach was further investigated by Trizotto et al, who focused on the effect of longitudinal train loads on fastener and rail loads ( 33 ). However, this model only accounted for the linear approximation of the load-displacement response of the track, and thus did not account for slip or the interaction of the applied vertical load.…”
Section: Previous Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This value is comparable to measured longitudinal modulus of vertically loaded ballasted track sections 38 and is believed to bound actual field conditions. Further, Trizotto et al 54 found that while there is a direct nonlinear relationship between longitudinal track modulus and fastener loads, a quadrupling of modulus was required to see a 30% increase in fastener load. Therefore, it is reasonable to believe that any small changes in longitudinal track modulus will have a small effect on the longitudinal fastener loads.…”
Section: Longitudinal Rail Seat Loadsmentioning
confidence: 99%
“…The analytical method developed by Kerr 27 and expanded by Trizotto et al. 54 quantifies longitudinal rail seat loads by assuming they are proportional to longitudinal rail displacement Equation (1) in the condition that there is no slip at the rail-fastener interface. Moreover, a parametric study was conducted to identify the effect of the superposition of multiple wheel loads and varying track stiffness.…”
Section: Data Interpretationmentioning
confidence: 99%